利对比教学法对连词“或者”与“还是” - Restu Adeliana Winandari; Lily Thamrin; Bun Yan Khjong (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2021)
AbstractIn the process of learning grammar, we will learn the division of function words. There are several types of function words, such as:prepositions, auxiliary words, and conjunctions.“Huo Zhe” and “Hai shi”are both conjunctions in chinese language.Although both “huo zhe” and “hai shi”denote the conjunctions of choice relations and have the same meaning, they are used in different contexts. “Huo Zhe”is often used in declarative sentences, and “Hai shi” is often used in interrogative sentences.For example, the author asked a question: I don't know if Annie can come to class today or not.The question the student gave the teacher was wrong. Under certain conditions, these two words can replace each other. Both words of them have the same understanding but are used under different conditions, but in certain conditions both words can be replaced,therefore in the use of disciples they often make some mistake . The researcher use Comparative Teaching Method to improve the capability of using these two words for Tanjungpura University students Chinese Language major class A to get increase until 29.4%,and this proves the teaching method is particularly appropriate for improving the capability of use these words.Keywords:“Huo Zhe” “Hai Shi”, Conjunction, Comparative Teaching Method